The Gut Microbiota of Critically Ill Patients With COVID-19 - Gaibani, Paolo; D’Amico, Federica; Bartoletti, Michele; Lombardo, Donatella; Rampelli, Simone; Fornaro, Giacomo; Coladonato, Simona; Siniscalchi, Antonio; Re, Maria Carla; Viale, Pierluigi; Brigidi, Patrizia; Turroni, Silvia; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
The SARS-CoV-2-associated COVID-19 pandemic has shaken the global healthcare system. Although the best-known symptoms are dry cough and pneumonia, viral RNA has been detected in the stool and about half of COVID-19 patients exhibit gastrointestinal upset. In this scenario, special attention is being paid to the possible role of the gut microbiota (GM). Fecal samples from 69 COVID-19 patients from three different hospitals of Bologna (Italy) were analyzed by 16S rRNA gene-based sequencing. The GM profile was compared with the publicly available one of healthy age- and gender-matched Italians, as well as with that of other critically ill non-COVID-19 patients. The GM of COVID-19 patients appeared severely dysbiotic, with reduced diversity, loss of health-associated microorganisms and enrichment of potential pathogens, particularly Enterococcus. This genus was far overrepresented in patients developing bloodstream infections (BSI) and admitted to the intensive care unit, while almost absent in other critically ill non-COVID-19 patients. Interestingly, the percentage of patients with BSI due to Enterococcus spp. was significantly higher during the COVID-19 pandemic than in the previous 3 years. Monitoring the GM of critically ill COVID-19 patients could help clinical management, by predicting the onset of medical complications such as difficult-to-treat secondary infections.